THE EFFECT OF CURRENT RATIO, DEBT TO ASSET RATIO AND TOTAL ASSET TURNOVER ON THE FINANCIAL PERFORMANCE OF BLUD AT CUT MEUTIA GENERAL HOSPITAL, NORTH ACEH DISTRICT - Rahmiatul Aula; Venna Maulida Mustika; Muhammad Multazam (RADJA PUBLIKA, 2023)
This study aims to see how much influence the Current Ratio, Debt to Asset Ratio, and Total Asset Turnover have on financial performance at Cut Meutia General Hospital, North Aceh Regency for the period 2016–2023. The data collection technique was carried out through documentation of the company's financial reports from 2016 to 2023, then further processed to calculate the financial ratios used as research samples. The statistical results also show that the Current Ratio (X1) has a t-value of 6.401 and a significance value of 0.003 <0.05, so it partially has a significant positive effect on financial performance. While the Debt to Asset Ratio (X2) has an F-value of -5.924 and a significance value of 0.004 <0.05, meaning that the Debt to Asset Ratio has a significant negative effect on financial performance. Total Asset Turnover (X3) has an F count value of 1.698 and a sig value of 0.54 > 0.05, meaning that Total Asset Turnover does not have a significant influence on financial performance. Simultaneously, Current Ratio (X1), Debt to Asset Ratio (X2), and Total Asset Turnover (X3) have an F count value of 15.310 with a significance value of 0.007 < 0.05, meaning they have a simultaneous influence on financial performance. This research is a quantitative research with an associative approach. Associative research aims to determine the relationship and influence between independent variables, namely Current Ratio (CR), Debt to Asset Ratio (DAR), and Total Asset Turnover (TATO), on the dependent variable, namely Financial Performance which is proxied by Return On Asset (ROA). Based on the financial report data of Cut Meutia General Hospital, North Aceh Regency for the period 2016–2023, the values of Current Ratio (CR), Debt to Asset Ratio (DAR), Total Asset Turnover (TATO), and Return on Asset (ROA) fluctuate annually. These changes indicate the dynamics in the condition of liquidity, solvency, activity, and profitability of the hospital during the study period. Current Ratio has a positive and significant effect on the financial performance of Cut Meutia General Hospital, North Aceh Regency, while Debt to Asset Ratio has a negative and significant effect on financial performance. Meanwhile, Total Asset Turnover does not have a significant effect partially. However, simultaneously, Current Ratio, Debt to Asset Ratio, and Total Asset Turnover have a significant effect on financial performance for the period 2016–2023.